PENGARUH PEMBERIAN DOSIS UREA DAN KONSENTRASI RHIZOBAKTERI BAMBU TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BUNCIS (Phaseolus vulgaris L.) - Maikel Omar Safuf; Maria Theresia Darini; Yekti Maryani (Universitas Sarjanawiyata Tamansiswa, 2018)
The aims of the study was to determine the right dosage of urea fertilizer and the concentration of bamboo rhizobacteria on the growth and yield of beans. This research was carried out in the prosperous central Lestari Makmur located in Agrorejo Village, Sedayu District, Bantul Regency, Special Region of Yogyakarta. The location of this study is altitude of ± 88 meters above sea level (mdpl), soil type is regosol, with soil pH of 5,5 - 6,7, the avarage temperature is 26-32 0C and rainfall 1,654.00 mm per year. This research was conducted in March until May 2018. The study was arranged in a factorial randomized complete block design (RAKL) of three replications. The first factor was the dose urea fertilizer (D) which consists of three levels, namely: 20, 30 and 40 kg per ha-1. The second factor was the concentration of bamboo rhizobacteria (R) which consists of three levels namely: 2.5; 5.0 and 7.5%, so that 27 treatment units are obtained. Observation variables include stem lenght, plant fresh weight, plant dry weight, number of pod per plant, pod lenght, pod weight per plot and pod weight per hectare. The results of the study were analyzed by variance at 5% real level, followed by Duncan’s Multiple Range Test at 5% level. The results showed there were an interaction between the dose of urea fertilizer and concentration bamboo rhizobacteria on pod weight per hectare of beans plants. The giving doses of urea fertilizer up to 40 kg ha-1 did not affect the growth and yield as well as the concentration of bamboo rhizobacteria up to 7,5%. The combination of 20 kg ha-1 urea fertilizer and 5,0% bamboo rhizobacteria concentration gave higher pod yield per hectare than the control (without treatment)